Detecting invertebrate ecosystem service providers in orchards: traditional methods versus barcoding of environmental DNA in soil. (7th April 2020) - Todd, Jacqui H.; Simpson, Robert M.; Poulton, Joanne; Barraclough, Emma I.; Villsen, Kurt; Brooks, Amber; Richards, Kate; Jones, Dan
Abstract: The objective of this study was to assess barcoding of environmental DNA as a method for monitoring invertebrate ecosystem service providers in soil samples. We selected 26 invertebrate ecosystem service providers that occur in New Zealand kiwifruit or apple orchards and produced mitochondrial cytochrome c oxidase gene subunit I (cytochrome oxidase I) and/or 28S ribosomal DNA sequences for each. Specific barcode primers were designed for each invertebrate ecosystem service provider and tested, along with generic barcoding cytochrome oxidase I primers, for their ability to detect DNA from invertebrate ecosystem service providers that had been added to sterilized and unsterilized soil samples. Although the specific primers accurately detected the invertebrate ecosystem service providers in more than 96% of the samples, the generic cytochrome oxidase I primers detected only 37% of the invertebrate ecosystem service providers added to the sterilized samples and 2.5% in the unsterilized samples. In a field test, we compared metabarcoding with traditional invertebrate trapping methods to detect the invertebrate ecosystem service providers in 10 kiwifruit and 10 apple orchards. All invertebrate ecosystem service providers were collected in traps in at least one orchard, but very few were identified by metabarcoding of soil environmental DNA. Although the specific primers can be used as a tool for monitoring invertebrate ecosystem service providers in soil samples, methodological improvements are needed before metabarcoding of soil environmental DNA can be used to monitor these taxa.